Fighting with FEMA : a practical regulations handbook - Martinet, Michael (New York : Routledge, Taylor & Francis Group, 2025)
"In this book, disaster finance and cost recovery expert Michael Martinet provides unparalleled coverage of the practical, real-world key principles necessary to successfully navigate the nuances of federal regulations surrounding FEMA's Public Assistance program. Accessibly written, Martinet demystifies the many policies, procedures, and administrative processes which a local government agency should adopt before a disaster which will prepare themselves for a greater financial recovery after a disaster. The intent is to awaken local authorities to the realities of the process and assist them in preparing for a day which all hope they will never see. Designed for financial officers, purchasing officials, Public Works officials, Building & Safety officials, public construction project managers and emergency management professionals at all levels of government, Fighting with FEMA will also earn a place in the libraries of consulting disaster recovery specialists and students interested in the financial aspects of disasters"--
FEMA's Public Assistance Program : overview -- General conditions for pre-emptive strategies -- Pre-disaster strategies & policies -- The local government cost recovery planning process -- Disaster cost accounting systems and details -- Work activity documentation & work process flow -- Criticality of effective/comprehensive documentation -- Pre-disaster and post-disaster photo documentation -- Disaster procurement -- Insurance and risk management -- Role of the EOC & department operations centers -- Hired guns & consultants -- Proclamation & declaration processes -- Debris monitoring & debris management -- Immediate needs funding -- Expedited projects for emergency work -- Community disaster loan program -- Mutual aid -- Local damage assessment process -- FEMA Preliminary Damage Assessment (PDA) -- Other Federal Agencies (OFA) funding -- FEMA authorized repair versus replacement (50% rule) -- Developing the A-list of projects aka the damage inventory -- Interpreting contracts, policies, and memoranda of understandings -- Eligibility -- Categorizing projects -- Beginning the paperwork process -- The Public Assistance Grants Portal -- Special considerations -- National Environmental Policy Act (NEPA) -- Direct administrative costs (DAC) -- Regional (& Personal) interpretation of FEMA regulations -- Building & infrastructure codes & standards -- Catch 22's : conflicting regulations -- Local agency self-inflicted gunshot wounds -- Private non-profit agencies -- Small Business Administration loans (for non-profits) -- Fraud -- Audits -- Appeals and arbitration -- Close outs and net small project overruns (NSPO) -- Summary and general rules.
Keywords: Public Assistance Grant Program (U.S.); United States. -- Federal Emergency Management Agency; Disaster relief -- United States -- Finance; Emergency management -- United States -- Finance; POLITICAL SCIENCE / General; SOCIAL SCIENCE / Disasters & Disaster Relief; POLITICAL SCIENCE / Government / Local